Assessment of the depth and rate of corrosion in steel reinforcement of reinforced concrete culverts - Vasiliev, Alexandr; Daškevič, Svetlana (International Conference “Environmental Engineering”, 2020)
Based on the results of many research years on concrete carbonisation: both immediately after manufacture (using heat-moisture treatment) and in reinforced concrete elements operated for the periods of various length (in an open atmosphere); the effect of carbonisation on the change in the protective properties of concrete in relation to steel reinforcement; for determination of the dependence of the corrosion state of steel reinforcement on the degree of concrete carbonisation in the area of steel reinforcement; the obtained regression dependences of the change (by time in the cross section) of the degree of concrete carbonisation of various classes in strength, – the analysis of the time of the onset of the boundary values of the degrees of concrete carbonisation (strength classes C12/15–C30/37) for the operating conditions of the open atmosphere was performed. Based on it, the regression dependences of the time variation of the depth of corrosion damage of steel reinforcement were construed (for fixed thicknesses of the concrete protective layer). The obtained nature of dependences made it possible to offer, in a general form, the regression dependences of the depth of corrosion damage and corrosion rate of steel reinforcement for concretes (strength classes C12/15–C30/37) for operating conditions in open atmosphere.